PENGEMBANGAN KREATIVITAS SISWA DI SDITNURUL ISLAM TENGARAN KABUPATEN SEMARANG - FARIDA, IDA NURUL (2010)
This study aims to describe (1) Management learning experience in the development of student creativity in Integrated Islamic Elementary School Nurul Islam, (2) Management of life skill in the development of student creativity in Integrated Islamic Elementary School Nurul Islam Semarang District. This research is a qualitative ethnographic design. Research carried on in Integrated Islamic Elementary School Nurul Islam Semarang District. Resource persons in this study were school principals and teachers. Data collection methods using depth interviews, observation and documentation. Data analysis using analysis are arranged in the site, with interactive models that start from (1) data reduction, (2) presentation of data, and (3) conclusion. To obtain valid data triangulation technique is carried out, both the source triangulation, triangulation methods and reviews of informants. This study shows that, (1) In a learning process, experience learning plays a very important role. A fun learning environment, conducive to appreciate the ability of children, involving children in various learning experiences will make children's understanding of new knowledge to survive much longer. Development of learning experiences in Intagrated Islamic Elementary School Nurul Islam has been well planned, varied, a conducive atmosphere, centered on children, and many activities involve children in various activities, encourage creativity development children in Integrated Islamic Elementary School Nurul Islam. (2) Development of a good life skill that children who are academic and non academic through regular learning activities, support activities with various facilities, as well as extra-curricular activities with a wide variety and choice and the means available to develop the creativity of children in Integrated Islamic Elementary School Nurul Islam Semarang District .